2022
DOI: 10.21037/jgo-22-198
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of 3D vascular reconstruction combined with 3D navigation in laparoscopic hepatectomy: systematic review and meta-analysis

Abstract: Background: Meta-analysis was used to compare the difference between 3D reconstruction technology and 2D computed tomography (CT) before surgery for primary hepatic carcinoma (PHC) and to systematically evaluate the application value of 3D vascular reconstruction and 3D navigation technology in guiding precise liver resection for PHC. However, there are still many controversies in this aspect, and there are no clear conclusions on the effectiveness and safety of three-dimensional vascular reconstruction combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Moreover, it has been reported that 3D reconstruction achieves better outcomes than 2D imaging. Jihua Jiang’s meta-analysis of 16 studies showed that the 3D liver reconstruction group was significantly superior to the conventional surgery group in terms of operation time and intraoperative blood loss ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that 3D reconstruction achieves better outcomes than 2D imaging. Jihua Jiang’s meta-analysis of 16 studies showed that the 3D liver reconstruction group was significantly superior to the conventional surgery group in terms of operation time and intraoperative blood loss ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al carried out a systematic meta-analysis to compare the difference between 3D reconstruction and 2D CT scans before surgery for primary hepatic carcinoma. They found that preoperative 3D reconstruction has a positive impact on liver surgery reducing damage to liver blood vessels, avoiding intraoperative bleeding during the operation, and achieving the accuracy of the tumor resection [ 6 ]. Moreover, 3D reconstruction in conjunction with 2D imaging could be a useful model for improving trainees’ understanding of liver anatomy and surgical resection [ 7 ].…”
Section: Use Of 3d Reconstructionmentioning
confidence: 99%
“…With great interest, we carefully read a recent paper written by Jiang et al entitled "Clinical efficacy and safety of 3D vascular reconstruction combined with 3D navigation in laparoscopic hepatectomy: systematic review and metaanalysis" (1), which was published in the latest issue of Journal of Gastrointestinal Oncology.…”
mentioning
confidence: 99%
“…Similarly, Park et al studied donors with separated right anterior and right posterior portal veins, whose cases also did not meet the requirements for being included in patients with PHC (3). In addition, in the inclusion criteria specified by the authors, the intervention of the control group was required to be 2D CT, but the intervention of Lim et al's control group was robotic liver resection, and Park et al's control group was equipped with the open hepatectomy, both of which were inconsistent with the intervention requirements for the control group (1,3,4). These problems may affect the conclusion of the article.…”
mentioning
confidence: 99%
See 1 more Smart Citation